Changes and innovations in livestock systems in Africa - (:unkn) unknown (My University, 2014)
In Africa, animal production is facing a significant demand evolution and is marked by many changes. In the future, livestock systems should be more productive and environmentally friendly. In order to do so breeders have to innovate. Agro-pastoral systems occupy an increasingly important place, pastoralism continues especially in arid areas and peri-urban and specialized breeding are gaining importance. Local and global changes, over the past 50 years, create more constraints but offer new opportunities. Innovations are at work. In pastoral areas, they mainly concern the management of resources and mobility of livestock, in agropastoral area diversification and crop-livestock integration, and in peri-urban area specialization and intensification of production. Difficult to detect, slow and incremental, innovations promote the mastery of change and should be encouraged and stimulated to meet the challenges of animal husbandry. The opportunities offered by the current realities of African husbandry (low productivity and rapid growth in demand) should guarantee a market and significant margins of progression. However, this can be achieved through the continuation of institutional reforms, the direct involvement of producer organizations, the terms of the market more secure, improved technical support.
Keywords: African Research